IMPLEMENTATION OF LITERATURE LEARNING AT MAN 3 SLEMAN: STRATEGIES AND READING INTEREST - Antarsyach, Anelka Almayda; Suryaman, Maman (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The existence of literature learning aims to support students' reading interests. Reading may seem like an easy activity, but in reality, the reading interest of Indonesian people remains relatively low. This study aims to examine the implementation of the literature learning program at MAN 3 Sleman, focusing on the strategies used and their effects on students' reading interest. This research employed a qualitative approach. Data were collected through observations and interviews with Indonesian language teachers (who also teach literature) and students. The study found that the literature learning strategies at MAN 3 Sleman were quite diverse but not yet optimal in fostering students' reading interests. internet resources and library book review activities, contribute to supporting students' interest in reading.